APROXIMACIÓN A LA TERMINOLOGÍA PROPIA DEL ÁMBITO DE LA HIPOACUSIA AUTOINMUNITARIA (ESPAÑOL, FRANCÉS, INGLÉS) - Rubio Gragera, María; Echeverría Pereda, Elena (Entreculturas. Revista de traducción y comunicación intercultural, 2016)
There are many experts who consider that, from the translation studies point of view, terminology is the most significant of a medical text. Hence our interest in researching about medical terminology. To do that, we have limited our field of research to an only one disease, the autoimmune inner ear disease, in three representative languages in this field: English, French and Spanish. This work aims at analyzing how medical terminology works in English, French and Spanish, focusing our attention on a very specific fiend (autoimmune inner ear disease). One of the results is the glossary which has been made from the terminological units (TU) contained on several entries that we have collected by alphabetic order. The results obtained could be useful for translators, terminologists or even specialists who, in more than one occasion, have to refer to publications written in different languages to update their knowledge or be informed about the new developments in there discipline.